2021
DOI: 10.1093/brain/awab403
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic FRA10AC1 variants cause a neurodevelopmental disorder with growth retardation

Abstract: The major spliceosome mediates pre-mRNA splicing by recognizing the highly conserved sequences at the 5’ and 3’ splice sites and the branch point. More than 150 proteins participate in the splicing process and are organized in the spliceosomal A, B, and C complexes. FRA10AC1 is a peripheral protein of the spliceosomal C complex and its ortholog in the green alga facilitates recognition or interaction with splice sites. We identified biallelic pathogenic variants in FRA10AC1 in five individuals from three consa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…In conclusion, our study provides an independent corroboration of the recently reported autosomal recessive FRA10AC1 -associated syndromic neurodevelopmental disease and growth retardation. 1 This syndrome is characterized by failure to thrive, microcephaly, global developmental delay, generalized hypotonia, feeding problems, agenesis of corpus callosum, and dysmorphic features with or without congenital heart disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In conclusion, our study provides an independent corroboration of the recently reported autosomal recessive FRA10AC1 -associated syndromic neurodevelopmental disease and growth retardation. 1 This syndrome is characterized by failure to thrive, microcephaly, global developmental delay, generalized hypotonia, feeding problems, agenesis of corpus callosum, and dysmorphic features with or without congenital heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recently reported cases presented with phenotypes similar to those in our patients. 1 They all had failure to thrive, microcephaly, global developmental delay, generalized hypotonia, feeding problems, brain anomalies (abnormal corpus callosum), and dysmorphic features with or without congenital heart disease ( Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene participates in causing the folate-sensitive fragile site via a tandem CGG repeat region, but for years little is known about its biological function. A recent study has just revealed that biallelic pathogenic variants FRA10AC1 might lead to delay in neurodevelopment but no de nite cellular function can be clari ed [25] . GPR85 is a brainspeci c G protein-coupled receptor with a conserved identical sequence discovered in both humans and mice [26] .…”
Section: Discussionmentioning
confidence: 99%
“…This indicates the possible role of FRA10AC1 in facilitating the recognition of or interaction between the acceptor and/or donor splice site and the branch point [ 19 ]. Interestingly, reminiscent of the clinical phenotypes caused by mutants of FMRP [ 12 , 13 ], clinical phenotypes have been reported that are caused by the biallelic loss of function variants of FRA10AC1 , which is characterized by strong intellectual disability and developmental delay [ 25 , 26 , 27 ]. Furthermore, in the context of a genome-wide association study (GWAS) aiming to identify genetic variants associated with amyloid-β 1–42 peptide levels in cerebrospinal fluid other than APOE ε4, as important biomarkers for Alzheimer’s disease, two FRA10AC1 SNPs—one intronic (a cis-eQTL) and one located less than 1kb upstream of the CGG repeat—were the top hits [ 28 ].…”
Section: Introductionmentioning
confidence: 99%